Frequency of disease-associated and other nuclear autoantibodies in patients of the German network for systemic scleroderma: correlation with characteristic clinical features - Mierau, Rudolf; Moinzadeh, Pia; Riemekasten, Gabriela; Melchers, Inga; Meurer, Michael; Reichenberger, Frank; Buslau, Michael; Worm, Margitta; Blank, Norbert; Hein, Rüdiger; Müller-Ladner, Ulf; Kuhn, Annegret; et al. (Arthritis Research & Therapy, 2011)
Introduction: In the present study, we analysed in detail nuclear autoantibodies and their associations in systemic sclerosis (SSc) patients included in the German Network for Systemic Scleroderma Registry. Methods: Sera of 863 patients were analysed according to a standardised protocol including immunofluorescence, immunoprecipitation, line immunoassay and immunodiffusion. Results: Antinuclear antibodies (ANA) were detected in 94.2% of patients. In 81.6%, at least one of the autoantibodies highly associated with SSc or with overlap syndromes with scleroderma features was detected, that is, anti-centromere (35.9%) or anti-topoisomerase I (30.1%), followed in markedly lower frequency by antibodies to PM-Scl (4.9%), U1-ribonucleoprotein (U1-RNP) (4.8%), RNA polymerases (RNAPs) (3.8%), fibrillarin (1.4%), Ku (1.2%), aminoacyl-transfer RNA synthetases (0.5%), To (0.2%) and U11-RNP (0.1%). We found that the simultaneous presence of SSc-associated autoantibodies was rare (1.6%). Furthermore, additional autoantibodies were detected in 55.4% of the patients with SSc, of which anti-Ro/anti-La, anti-mitochondrial and anti-p25/p23 antibodies were most frequent. The coexistence of SSc-associated and other autoantibodies was common (43% of patients). SSc-associated autoantibodies disclosed characteristic associations with clinical features of patients, some of which were previously not acknowledged. Conclusions: This study shows that five autoantigens (that is, centromere, topoisomerase I, PM-Scl, U1-RNP and RNAP) detected more than 95% of the known SSc-associated antibody responses in ANA-positive SSc patients and characterise around 79% of all SSc patients in a central European cohort. These data confirm and extend previous data underlining the central role of the determination of ANAs in defining the diagnosis, subset allocation and prognosis of SSc patients.
Gesehen am 19.08.2022